PUSPA RAKSAKA JAGAD; DESIGN OF ECO-FRIENDLY FASHION INNOVATIONS IN CHILDREN’S KEBAYA - Leliana Sari, Dewa Ayu Putu (International Journal of Social Science, 2025)
This research explores the concept of Puspa Raksaka Jagad, which involves creating children's kebaya based on eco-friendly principles by integrating upcycling techniques from thrifted clothing and ecoprinting using natural dyes derived from ylang-ylang, frangipani, and hibiscus flowers. The aim of this research is to produce children's kebaya that are not only aesthetically pleasing and comfortable to wear, but also environmentally friendly and sustainable. The methods employed include exploring recycled materials in the form of thrifted clothing, designing kebayas with unique ecoprint motifs, and creating products through the ecoprint pounding technique, which utilizes natural pigments from local plants. The results of the study show that the use of upcycling and ecoprint pounding techniques can produce children's kebaya with high aesthetic value, while reducing textile waste and the use of synthetic chemicals. This product also makes a positive contribution to cultural and environmental preservation. Puspa Raksaka Jagad is a children's fashion innovation that prioritizes sustainability, creativity, and local wisdom.